2015
DOI: 10.3892/mmr.2015.4353
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin inhibits the proliferation of myelodysplastic syndrome cells through the induction of cell cycle arrest and apoptosis

Abstract: The present study aimed to assess the effects of the flavonoid, wogonin, and its underlying mechanism on myelodysplastic syndrome (MDS) in SKM-1 cells. In the present study, wogonin inhibited the cell proliferation of SKM-1 cells in a dose- and time-dependent manner, with the concentration required to yield a half maximal inhibitory concentration (IC50) of 212.1 µmol/l at 24 h, and 43.4 µmol/l at 72 h. Furthermore, wogonin induced cell cycle arrest at the G0/G1 phase and induced the apoptosis of the SKM-1 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Western blot analysis was performed as described previously ( 7 ). Briefly, aliquots of cell lysates containing 25 µg protein were separated by sodium dodecyl sulfate polyacrylamide gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as described previously ( 7 ). Briefly, aliquots of cell lysates containing 25 µg protein were separated by sodium dodecyl sulfate polyacrylamide gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…5,7-dihydroxy-8-methoxyflavone, or wogonin, is a naturally-derived ingredient isolated from the roots of Scutellaria baicalensis Georgi, commonly known as Huang-Qin. In traditional Chinese medicine, this substance has been used to treat allergies, inflammatory diseases and tumors (11)(12)(13). Previous studies have demonstrated that wogonin suppresses LPS-induced expression of iNOS, tumor necrosis factor-α (TNF-α), NO, and IL-1β in microglia via inhibition of NF-κB activation (14,15).…”
Section: Wogonin Protects Human Retinal Pigment Epithelium Cells Frommentioning
confidence: 99%
“…Western blot analysis. cell protein extraction and western blot analysis were performed as described previously (25). Briefly, following treatment with luteolin, as described in the dNA fragmentation experiments, the total protein content of the cytosolic fraction in the supernatant was isolated from the harvested cells and measured using a BcA protein assay.…”
Section: Determination Of δψMmentioning
confidence: 99%